2011
DOI: 10.3892/or.2011.1264
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid suppresses the migration and invasion of PC-3 human prostate cancer cells via inhibition of matrix metalloproteinase-2 and -9 signaling pathways

Abstract: Abstract. epidemiological studies have demonstrated that a natural diet or consumption of fruits or vegetables can decrease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 46 publications
(60 reference statements)
2
29
0
Order By: Relevance
“…The simultaneous antioxidant and antiproliferative effects observed may be ascribed to their rich content of phenols and flavonoids [10, 41]. In fact, gallic acid [42, 43] and rutin [44] in both EtOAc and n -BuOH extracts and catechins [17, 45] in the EtOAc extract are present within significant amounts and are known for their antioxidant and antiproliferative activity. In fact, the literature demonstrates that often natural compounds can act as both antioxidants and anticancer agents, taking advantage of the particular redox environment and signaling pathways in cancer cells [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous antioxidant and antiproliferative effects observed may be ascribed to their rich content of phenols and flavonoids [10, 41]. In fact, gallic acid [42, 43] and rutin [44] in both EtOAc and n -BuOH extracts and catechins [17, 45] in the EtOAc extract are present within significant amounts and are known for their antioxidant and antiproliferative activity. In fact, the literature demonstrates that often natural compounds can act as both antioxidants and anticancer agents, taking advantage of the particular redox environment and signaling pathways in cancer cells [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were harvested from each treatment then were washed with cold PBS and then scraped and washed twice by centrifugation at 1,000xg for 5 min at 4°C. All pellets were individually resuspended in the PRO-PREP protein extraction solution (iNtRON Biotechnology, Seongnam, Gyeonggi-Do, Korea) for 3 h at −20°C, as described previously [33, 34]. The lysate from each sample was collected by centrifugation at 12,000 ×g for 30 min at 4°C, and the supernatant was stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on MCF-7 breast cancer cells also showed that gallic acid treatment inhibited cell proliferation (IC 50 80.5 µM) and induced apoptosis via both the extrinsic and intrinsic pathways [150]. Additionally, exposure to gallic acid (25 and 50 μM) suppressed the invasion and migration of PC-3 prostate cancer cells through down-regulation of MMP-2 and MMP-9 [154]. In another study, gallic acid (50, 100, and 200 μM) in PC-3 prostate cancer cells provoked DNA damage and inhibited expression of DNA repair genes, which contributed to gallic-induced growth inhibition [155].…”
Section: Experimental Studiesmentioning
confidence: 99%